2018
DOI: 10.4103/jomfp.jomfp_11_17
|View full text |Cite
|
Sign up to set email alerts
|

Oral rhabdomyosarcoma in an adult male: A rare case report

Abstract: Rhabdomyosarcoma is a malignant neoplasm of mesenchymal cells, showing varying degrees of striated muscle cell differentiation. It predominantly occurs in children while rarely found in adults and involvement of the oral cavity accounts for only 10%–12% of all head-and-neck cases. Herewith, we present a rare case of spindle cell rhabdomyosarcoma in a 52-year old male, involving the mandibular gingiva, and describe the clinical, radiological, histopathological and immunohistochemical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…RMS is the most common soft tissue sarcoma in children, with an annual incidence of 4.5 cases per 1 million children [ 8 ]. In contrast, it is rare in people older than 45 years and comprises only 2–5% of soft tissue sarcomas in adults [ 4 ]. The incidence of RMS differs by age, histology, and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RMS is the most common soft tissue sarcoma in children, with an annual incidence of 4.5 cases per 1 million children [ 8 ]. In contrast, it is rare in people older than 45 years and comprises only 2–5% of soft tissue sarcomas in adults [ 4 ]. The incidence of RMS differs by age, histology, and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In parts of Asia such as Japanese, Indian, and Chinese populations, the incidence of RMS appears to be lower than it is in Europe and the United States [ 9 ]. The common sites of occurrence are the head and neck region (35%), genitourinary tract (23%), retroperitoneum, and the extremities (17%) [ 4 ]. In the head and neck region, the commonly affected sites are the orbit, paranasal sinuses, and the neck [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral cavity as a primary site of RMS is rare with few studies reporting involvement of soft palate, tongue, buccal mucosa, maxillary sinus, and posterior region of mandible. 6 Chen et al (2015) reported seven cases, out of which only one had occurred on the palate. 5 The reported cases are generally aggressive lesions extending to the adjacent alveolus, soft palate, oropharynx and nasopharyngeal areas.…”
Section: Discussionmentioning
confidence: 99%